2014
DOI: 10.11113/jt.v70.3536
|View full text |Cite
|
Sign up to set email alerts
|

Kaedah Penggantian Tanah untuk Meningkatkan Kekuatan Struktur Tanah di Kawasan Tanah Jerlus

Abstract: Soft soil in rice field has a hardpan layer of less than 0.3Mpa. The usage of farm mechanization in rice field cannot be performed due to the hardpan structure cannot accommodate the load of heavy machinery. To overcome this problem, the method of soft soil replacement is used in order to revitalize the hardpan layer which has been damaged due to the stagnant water problem. Field study was conducted to test the soft soil replacement method to solve the problem of land on soft soil plot in Alor Senibung. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Both paddy blocks have been experienced with low rice yield due to soft clay soil problems (Nordin et al, 2014). The occurrence of soft clay soil in the study area caused the agricultural machines could not be operated over the field because the soil was not able to resist the mechanical pressure (Nasir et al, 2019). In this study, we used a grid sampling method to collect soft clay soil samples in each paddy block.…”
Section: The Study Area and Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both paddy blocks have been experienced with low rice yield due to soft clay soil problems (Nordin et al, 2014). The occurrence of soft clay soil in the study area caused the agricultural machines could not be operated over the field because the soil was not able to resist the mechanical pressure (Nasir et al, 2019). In this study, we used a grid sampling method to collect soft clay soil samples in each paddy block.…”
Section: The Study Area and Soil Samplingmentioning
confidence: 99%
“…For instance, Hore et al (2020) has successfully created a model for zonation of soft clay soil. Nasir et al (2019) has reported the rubber wheel tractors and half-track tractors can devastate the soil hardpan layer and may cause soft soil spots around the paddy fields. Nordin et al (2014) has recommended the soil replacement technique to improve the soil hardpan layer in the soft clay soil areas.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisation has been credited with boosting the productivity of paddy production, but it has also been accused of contributing to the development of soft soil conditions. Soft soil conditions are characterised by high compressibility and low strength, with a hardpan layer at a soil depth of 30 cm that measures less than 0.3 MPa (Nordin et al, 2014;Rendana et al, 2017). Soft soil condition is caused by the extensive use of heavy field machinery which damages the soil hardpan layer.…”
Section: Introductionmentioning
confidence: 99%
“…Soft soil condition has become a major issue faced by paddy farmers (Taufik et al, 2015). Soft soil is defined as an area with low and inadequate bearing capacity, having less than 0.3 MPa at 30 cm depth, to support the agricultural machineries on it (Ahmad et al, 2020;Fauzi et al,2018;Rendana et al, 2017;Nordin et al, 2014). In 2013, 8000 hectares of soft soil areas were identified in MADA, 4800 hectares in KETARA and 5200 hectares in IADA Kemasin Semerak (Abdullah, 2014).…”
Section: Introductionmentioning
confidence: 99%